Hindu-muslim religious encounter in Bangladesh : a case study of Dhaka - Rahman, Md. Asadur (Kulliyyah of Islamic Revealed Knowledge and Social Sciences, International Islamic University Malaysia, 2016)
This study investigates the present condition of Hindu-Muslim relations in Bangladesh, a multi religious country in South Asia with Muslim majority. It is based on in-depth interview with 18 Hindu and 18 Muslim respondnets in Dhaka, the capital city. Among these 18 from each category, the type of the respondents the researcher has selected is religious scholars, cultural activists, and educationists cum community representatives. The study aims to justify the propagations and sense of Hindu-Muslim confrontation as reflected in many narratives and literatures where an attempt to portray the felt absence of interreligious harmony. The in-depth interviews emphasize religious issues, includes religio-cultural and socio-political mtters which manifested in the relationships. As such, the study explores the current scenario of relations between these two communities which opposes present-day literatures and narratives which depict friendship and intimacy among those who are living peacefully and harmoniously. In the study, special attention is given to issues relating to commonly held causes for the decline of the Hindus in Bangladesh as widely believed by Hindu and Muslim alike. Both Hindu and Muslim respondents are asked to describe what they think are causes for the decrease of their number. Surprisingly the data analyzed, nullifies the common supposition that torture of Hindu is reason for the decrease. It is therefore found to be a myth or a mere speculation. Denying this, the study shows that the widely believed assumption of Hindu decline has been challenged. Most importantly, it indicates that the Bangla language, spoken by both Hindu and Muslims in their daily lives, –as the study has examined- has played a fundamental role in the process of Islamization to its speakers irrespective of their ethnic backgrounds. And last but not least, it is found through their narratives that religion is an inevitable element for peace and stability for in the context of Bangladesh, religion, as such, significantly contributes to the making of good citizens, an essential element for co-existence and interreligious harmony.